Binding of Kebuzone to Human Serum Albumin Studied by High Performance Liquid Affinity Chromatography - Zhivkova, Zvetanka D; Russeva, Veska N (Arzneimittelforschung, 2000)
The binding of the anti-inflammatory agent kebuzone (CAS 853-34-9) to human serum albumin (HSA) was examined by means of high performance liquid affinity chromatography. Phenylbutazone and diazepam, the binding properties of which were an object of our previous work, were used as markers for the major supposed binding sites on HSA. It was established that kebuzone binds to the high-affinity phenylbutazone binding sites as well as to the low-affinity diazepam binding sites. The estimated values of the equilibrium affinity constants were 5.9 e 104 1/mol and 1.7 103 1/mol, respectively, suggesting a low binding affinity for kebuzone. A stepwise mechanism of the binding process could be proposed: primary at phenylbutazone sites, and secondary at the diazepam sites. The binding behavior of kebuzone was very similar to that of the structurally related compound phenylbutazone. The observed lower affinity is well explained in view of the lower lipophilicity of kebuzone.
Keywords: CAS 853-34-9; Human serum albumin; Kebuzone, affinity chromatography, protein binding